2015
DOI: 10.1186/s12872-015-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of periostin in diabetic cardiomyopathy and the effect of valsartan

Abstract: BackgroundPeriostin, an extracellular matrix protein, plays a significant role in adverse cardiac remodeling. However, no report has documented the function of periostin in left ventricular remodeling of streptozototin (STZ)-induced diabetic rats. The aim of the present study was to observe the expression of periostin in Wistar rat’s myocardium of diabetic cardiomyopathy (DCM) and the effect of valsartan on it.MethodsImmunohistochemistry, real-time polymerase chain reaction, and Western blot analysis were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Several previous studies have indicated a link between high glucose exposure and periostin expression [23,24]. In this study, we showed that ectopic expression of periostin prevented high glucose-induced apoptotic response in HUVECs, as determined by TUNEL staining and caspase-3 activity assay.…”
Section: Discussionsupporting
confidence: 54%
“…Several previous studies have indicated a link between high glucose exposure and periostin expression [23,24]. In this study, we showed that ectopic expression of periostin prevented high glucose-induced apoptotic response in HUVECs, as determined by TUNEL staining and caspase-3 activity assay.…”
Section: Discussionsupporting
confidence: 54%
“…Lower periostin levels may suggest a reduced ability to undergo adaptive ventricular remodelling among patients with diabetes compared with patients without diabetes. In previous rat studies of diabetic cardiomyopathy, myocardial expression of periostin was higher . The finding of lower periostin in our study may reflect differences in location of periostin measurement (serum vs. myocardium) or clinical state (acute vs. chronic HF).…”
Section: Discussionsupporting
confidence: 41%
“…Our results extend upon work from existing experimental models. In diabetic rats, compared with controls, periostin is closely associated with ventricular fibrosis and adverse cardiac remodelling . The use of valsartan in diabetic rats significantly improved ventricular remodelling and markers of fibrosis by possibly targeting the periostin pathway .…”
Section: Discussionmentioning
confidence: 97%
“…Periostin was significantly elevated along with other TGF markers, such as TGF‐β1, TGF‐β1 R II, and Type I and III collagens in the myocardium of diabetic rats compared with control group . In streptozotocin (STZ)‐induced type 1 diabetic mice model, enhanced reactive oxygen species (ROS) production, activation of extracellular regulated kinase (ERK), TGF‐β, periostin pathway, and myocardial fibrosis resulted in important consequences in mice with DCM.…”
Section: Resultsmentioning
confidence: 99%